Correctional fundamentals: a personal narrative approach - Griffin, O. Hayden (Carolina Academic Press, 2019)
A brief history of American corrections -- Philosophies of corrections -- Law of corrections -- Incarceration -- Probation and parole -- Community corrections -- Correctional facility life -- Juvenile corrections -- Correctional facility workers -- Rehabilitation programs.